Organizational diagnostics: a systematic approach to identifying technology and workflow issues in clinical settings. Issue 2 (20th April 2020) - Unertl, Kim M; Novak, Laurie Lovett; Van Houten, Courtney; Brooks, JoAnn; Smith, Andrew O; Webb Harris, Joyce; Avery, Taylor; Simpson, Christopher; Lorenzi, Nancy M
Abstract: Objectives: Healthcare organizations need to rapidly adapt to new technology, policy changes, evolving payment strategies, and other environmental changes. We report on the development and application of a structured methodology to support technology and process improvement in healthcare organizations, Systematic Iterative Organizational Diagnostics (SIOD). SIOD was designed to evaluate clinical work practices, diagnose technology and workflow issues, and recommend potential solutions. Materials and Methods: SIOD consists of five stages: (1) Background Scan, (2) Engagement Building, (3) Data Acquisition, (4) Data Analysis, and (5) Reporting and Debriefing. Our team applied the SIOD approach in two ambulatory clinics and an integrated ambulatory care center and used SIOD components during an evaluation of a large-scale health information technology transition. Results: During the initial SIOD application in two ambulatory clinics, five major analysis themes were identified, grounded in the data: putting patients first, reducing the chaos, matching space to function, technology making work harder, and staffing is more than numbers. Additional themes were identified based on SIOD application to a multidisciplinary clinical center. The team also developed contextually grounded recommendations to address issues identified through applying SIOD. Discussion: The SIOD methodology fills a problem identification gap in existing process improvement systems through an emphasis on issue discovery, holistic clinic functionality, and inclusion of diverse perspectives. SIOD can diagnose issues where approaches as Lean, Six Sigma, and other organizational interventions can be applied. Conclusion: The complex structure of work and technology in healthcare requires specialized diagnostic strategies to identify and resolve issues, and SIOD fills this need.